Legal Certainty and the Protection of Street Children: A Socio-Legal Inquiry into Local Governance in Indonesia - Aliffi’a Kursiya Jamil; Afrik Yunari (Rule of Law Studies Journal, 2025)
Abstrak   Background: Street children’s protection is often discussed as if good regulations are enough, yet legal certainty rarely follows from text alone. In Indonesia, local governments are expected to convert child protection mandates into routine safeguards while facing capacity constraints, coordination frictions, and entrenched social vulnerability. Aims: This study explores how legal certainty is formed in everyday governance practices related to the protection of street children in Indonesia. It considers whether legal certainty functions as a dependable guarantee of rights or remains contingent on institutional choices and implementation patterns. Methods: A socio-legal approach was adopted by linking normative analysis of statutes, local regulations, and policy documents with empirical inquiry. The empirical component was developed through qualitative interviews and observation involving local government personnel engaged in child protection services and other relevant stakeholders, allowing the study to read legal promises alongside administrative practice. Result: The findings indicate that predictability in protection is shaped more by procedural consistency, coordination, and follow-through than by the wording of norms. Local frameworks commonly require mechanisms such as structured case recording, round-the-clock complaint channels, temporary shelters, and rehabilitation or care facilities, yet these measures are applied unevenly across cases. Variation in coordination and shifting priorities weakens the practical certainty that street children can expect when seeking protection and services. Conclusion: Legal certainty in this field should be understood as a governance outcome produced through institutional action, not merely as an attribute of written law. Strengthening it calls for tighter institutional alignment, clearer implementation pathways, and accountable mechanisms that are responsive to social vulnerability.